Cytopathology of Liver, Biliary Tract, Kidney and Adrenal Gland - Erozan, Yener S.; Tatsas, Armanda (Essentials in Cytopathology, 2015)
This volume fulfills the need for an easy-to-use and authoritative synopsis of intra-abdominal organ cytopathology.  Part of the Essentials in Cytopathology book series, the book is heavily illustrated with a full color art program, while the text follows a user-friendly outline format.  The book  also fits into the lab coat pocket and is ideal for portability and quick reference.   Written by authorities in the field, Cytopathology of the Liver, Biliary Tract, Kidney and Adrenal Glands is a concise and valuable resource to pathologists on the subject of intra-abdominal organ cytopathology.